Detection of Herpes Simplex Virus-1 Antigen in Tissues of Breast Cancer - Khashman , Basim Mohammed (Diyala Journal of Medicine, 2019)
Background: Breast cancer is a common malignancy and a major cause of death in women. Many factors responsible for breast cancer such as viruses. Herpes simplex virus-1 (HSV-1), infection which has been implicated in pathogenesis of certain disease and some studies has been described the involvement of viruses in cancers. Aim: To determine the presence of HSV-1antigen in women presented with breast cancer. Methods: Twenty two formalin-fixed paraffin embedded breast tissue collected from the Al-Kadhimiya teaching hospital in Baghdad. Clinical data were analyzed from the medical records; in addition ten normal breast tissues used as control group. All samples were sectioned and examined by direct immunofluorescence for detection of HSV-1 antigen. Results: Detection of HSV-1 Ag in tissues patients with breast cancer was 31.8% (7 out of 22), where statistical significant was found between expression of HSV-1 and patients with breast cancer based on statistical analysis. While no significant correlation between HSV-1 and age, grade, type of tumor and lymph node metastasis. Conclusion: Based on the results of the current study, Herpes simplex virus-1 could be a co-factor in the oncogenesis of breast cancer or could infect cancer tissues opportunistically.